Programa deltagen como ferramenta no melhoramento genético em gado de corte - Paula Dias Ribeiro, Ana (Universidade Federal do Tocantins, 2022)
The present work refers to the activities carried out during the period of supervised curricular internship, presenting as a topic of interest the use of the DeltaGen program as a toolfor genetic improvement in beef cattle, monitored in the the same period. The internship was held from January 19 to March 1, 2021, with a workload of 8 hours per day, resulting in 416 hours, under the supervision of Veterinarian Rodrigo Rodrigues Assis. During the internship, monitoring activities were mostly done in the reproduction area on bovine females, such as evaluation of cyclicity and gynecology in heifers, ultrasound examination, estrus synchronization, fixed-time artificial insemination (IATF) and resynchronization. Also including also assistance on cases of mastitis, herniorrhaphy and rectal prolapse. Due to the partnership of the store Agrocerrado Nutrição e Agronegócios with the Santa Tereza II farm, it was possible to monitor selection management on the property. Nevertheless, activities were not restricted only to those areas, it was extended to sales consultancy, software and sales techniques training, budgets and internal purchases,stock management and control, feeding formulation and technical visits in loco.